Acute otitis media: clinical course among children who received a short course of high dose antibiotic. Issue 6504 (2nd November 1985) - Bain, J; Murphy, E; Ross, F
Abstract : A prospective study was carried out in 274 children aged 3 to 10 years with acute otitis media. They were randomly allocated to one of two treatment regimens: (a) a seven day course of amoxycillin 125 mg three times a day, and (b) a two day course of amoxycillin 750 mg twice a day. They were followed up by symptom diaries and clinical examination. The findings in the 243 children who completed the trial showed that the short course of treatment was as effective as the seven day course in the speed of resolution of symptoms and signs, irrespective of previous history of otitis media or of episodes in which bulging of the eardrums was observed at presentation. A subgroup of 185 children was followed up for one year after entry to the trial. During this period no appreciable differences emerged between the two antibiotic regimens, either in recurrence rate of otitis media or in the frequency of hearing loss at one month and six months after entry to the study. Side effects of treatment were few, and those that could be attributed to antibiotic use occurred with equal frequency in the two treatment groups.